2017
DOI: 10.3892/ijo.2017.3855
|View full text |Cite
|
Sign up to set email alerts
|

Early growth response 3 inhibits growth of hepatocellular carcinoma cells via upregulation of Fas ligand

Abstract: Abstract. Hepatocellular carcinoma (HCC) is a prevalent malignancy with aggressive biological behavior and poor prognosis. Early growth response 3 (EGR3) is a zinc finger transcription factor, and has been studied primarily in the context of neurodevelopment, autoimmunity, inflammation and angiogenesis. Accumulating evidence indicates that EGR3 is a novel suppressor gene of tumor initiation and progression in certain cancer events, but little work has been carried out in exploring the relationship between EGR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Early growth response 3 (EGR3), as a novel zinc finger transcription factor, is a newly discovered tumor suppressor gene, which can inhibit the growth of hepatocellular carcinoma, gastric cancer, and other cancer cells by up-regulation of Fas ligand [77]. Zhang et al [78] found that the low levels of EGR3 were significantly discovered in hepatocellular carcinoma tissues and various hepatoma cell lines (PLC/PRF/5, HCC-LM3, Huh7, and HepG2), but could be explored in human normal hepatic cell lines (L02). The experimental results of nude mouse models showed that the expression of FasL in xenograft tumor tissues with high expression of EGR3 was also significantly increased.…”
Section: Fasl Expressed On Nk Cells Exerts Anti-hepatocarcinoma Activmentioning
confidence: 99%
“…Early growth response 3 (EGR3), as a novel zinc finger transcription factor, is a newly discovered tumor suppressor gene, which can inhibit the growth of hepatocellular carcinoma, gastric cancer, and other cancer cells by up-regulation of Fas ligand [77]. Zhang et al [78] found that the low levels of EGR3 were significantly discovered in hepatocellular carcinoma tissues and various hepatoma cell lines (PLC/PRF/5, HCC-LM3, Huh7, and HepG2), but could be explored in human normal hepatic cell lines (L02). The experimental results of nude mouse models showed that the expression of FasL in xenograft tumor tissues with high expression of EGR3 was also significantly increased.…”
Section: Fasl Expressed On Nk Cells Exerts Anti-hepatocarcinoma Activmentioning
confidence: 99%
“…Note worthily, the abnormal expression of EGR3 is also observed in liver cancer. Zhang et al [16] showed that the expression of EGR3 is frequently down-regulated in HCC tissues and cell lines, and the ectopic expression of EGR3 inhibits the proliferation and induce the apoptosis of HCC cells in vitro. In this study, EGR3 was identified as a target of miRNA-210.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 4046 transcripts containing 5853 sites were predicted. A target gene EGR3 (ENST00000317216.2) was selected due to its anti-tumor role on liver cancer [16].…”
Section: Targetscan Predictionmentioning
confidence: 99%
“…Note worthily, the abnormal expression of EGR3 is also observed in liver cancer. Zhang et al 16 showed that the expression of EGR3 is frequently down-regulated in HCC tissues and cell lines,…”
Section: Discussionmentioning
confidence: 99%
“…A total of 4046 transcripts containing 5853 sites were predicted. A target gene EGR3 6 (ENST00000317216.2) was selected due to its anti-tumor role on liver cancer 16 .…”
Section: Targetscan Predictionmentioning
confidence: 99%